CHILDREN’S ALCOHOLISM AS A SOCIAL AND PEDAGOGICAL PROBLEM. DRUG ADDICTION AS A FORM OF DEVIANT BEHAVIOR - Jumayeva Farangiz Ilhom qizi; Tovarova Munisa Ulug'bek qizi; Hayodmurodova Sevinch Faxriddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the widespread cases of alcoholism and drug addiction among children from a socio-pedagogical perspective. The author deeply studies the factors of drug addiction as a form of deviant behavior, the role of the social environment and educational gaps. The article proposes a solution to the roots of the problem based on theoretical and practical approaches. Proposals are put forward aimed at pedagogical monitoring, strengthening school-family cooperation, and developing social and emotional health in children.